INVESTIGATION OF SOLUTION RECOMMENDATIONS DEVELOPED BY PROSPECTIVE TEACHERS ON DIGITAL ADDICTION SCENARIOS - Sanal, Seda Ozer; Torun, Fulya; Dargut, Tülay (My University, 2023)
Digital addiction, which negatively affects the physical and psychological health of individuals and gradually spreads to different areas, is a problem that needs to be resolved for all organizations that care about individuals. Understanding, solving and developing interventions to reduce this problem is critical for a healthy social culture at macro scale and for the life of a healthy individual at micro scale. Digital addiction is a situation that can be seen in all areas of life and in all age groups. In this study, digital addiction scenarios were produced by wondering how digital addiction can be solved from the perspective of teacher candidates. It has been possible to evaluate the awareness, knowledge and competencies of the pre-service teachers with the solution suggestions they brought to the digital addiction scenarios. The solution suggestions produced by the pre-service teachers for the addiction problem of a digitally addicted student were gathered under the themes of detection, intervention and support, domestic arrangements, information and awareness raising, socialization and communication, and follow-up and observation. After the thematic analysis of these solution proposals, themes and sub-themes were created and the themes were discussed in the light of the literature.
Keywords: Problem solving; prospective teachers; scenario; digital addiction